Steroid Sensitive Nephrotic Syndrome Associated with Situs Inversus Totalis in a Child : A Case Report with Review of Literature - Suchi Acharya; Alluri Deepthi; Manish Kumar (Indian Pediatrics Case Reports)
Background: Situs inversus (SI) totalis is a rare congenital anomaly characterized by complete inversion of abdominal and thoracic visceral organs. While renal abnormalities have been documented in such cases, the association with nephrotic syndrome (NS) is exceptionally rare. Clinical Description: A 2.5-year-old girl, diagnosed with NS, a year ago, presented with anasarca due to relapse. Routine clinical examination showed normal vital parameters, anthropometry, mild pallor, and pitting edema. While abdominal examination revealed ascites, cardiovascular examination was suggestive of dextrocardia which was confirmed by echocardiogram without structural heart defects. Ultrasound abdomen liver, spleen, and stomach showed lateral inversion. Laboratory investigations were consistent with a relapse of NS. Management and Outcome: The child was managed with corticosteroids along with anti-edema measures, resulting in remission. Conclusion: This case brings out the exceptional rarity of SI totalis coexisting with NS and encourages further research into potential genetic and immunological factors which may explain this coexistence.